Optimization of HIB Value Combination of Tween 60 and Span 80 on Cream Formulation of Ethanol Extract of Green Tea Leaves (Camellia Sinensis L.) - Fransiska Lisa Anindya Putri; Akhmad Kharis Nugroho; Erna Prawita Setyowati (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Green tea (Camellia sinensis L.) is known to have ability to protect skin against free radicals. This is supported by polyphenol compound catechin. This research aims to determine the optimum Hydrophilic-Lipophilic Balance (HLB) value of Tween 60 and Span 80 compositions on the optimum cream formula of ethanol extract of green tea leaves. Tea leaves are extracted by macerating using 70% ethanol. Catechin in extract is known from Thin Layer Chromatography (TLC) test with silica gel 60 F254 as stationary phase and ethyl acetate:aquadest:formic acid (18:1:1 v/v) as mobile phase. Antioxidant activity is determined by 2,2-Diphenyl-1-picryhydrazyl (DPPH) method and value of Inhibition Concentration 50% (IC50) is then calculated. Formula optimization using Design Expert® version 7.1.5 (DX 7) software, Simplex Lattice Design (SLD) method with two components Tween 60 and Span 80. Cream is characterized according to physical properties organoleptic, homogeneity, viscosity, pH, spreadability, adhesiveness, and cream type. The optimum formula obtained is then tested for physical stability for 4 weeks at room temperature (28±2°C) and data are statistically analyzed using one-way ANOVA. The extract contains catechin proved with Retention factor (Rf) value 0.8 and has antioxidant activity with IC50 value 56.35 ppm. 6.4% Tween 60 and 3.6% Span 80 result an optimum HLB value 11.1. It has viscosity 2897.50±35.94 mPa.s, spreadability 18.44±0.06 cm2, adhesiveness 0.85±0.05 seconds, and pH 4.530±0.002. Statistical test shows that the cream is significantly altered at pH, but does not significantly change in viscosity, spreadability, and adhesiveness after being stored for 4 weeks.